TAREQAT KHALWATIYAH SAMMAN DI DESA TONGKE-TONGKE KEC. SINJAI TIMUR (Eksistensi dan Penyebaran Ajarannya) - Anis Anis; Desi Alawiyah; Burhanuddin Burhanuddin (Universitas Islam Ahmad Dahlan, 2020)
In this study, the implementation of Friday Prayers and Sermons at Sinjai (Phenomenon of Hanging Out outside the Mosque during Khutbah), there are two frameworks that are the focus of research, namely: first, analysis of the conception of the implementation of Friday prayers and sermons based on the arguments of the Qur'an. 'an- Hadith, the paradigm of Friday prayers and sermons from the perspective of religious fiqh schools. Second, the habit of hanging out outside the mosque during the sermon. This study seeks to find the problem that causes this phenomenon to become a reality that tends to be traditional in all mosques where Friday prayers are held in Sinjai Regency. This research uses a qualitative approach to sociological, anthropological, and theological theories. In addition, in the discussion of this research there will be recommendations for problem solutions or alternative steps that can be achieved overcoming the problem. So the results of this study suggest that the Friday Prayers and the Khutbah are an inseparable part of the worship procession on Friday. The existence of the sermon in the Friday prayer procession is very clear in terms of the basis of the arguments and wisdom contained therein for the Muslims. Therefore, the implementation of the prayer procession and Friday sermons requires management from the mosque administrators / ta'mir. For this reason, it is important to have a written concept regarding the planning, implementation and evaluation of the implementation of Friday prayers and sermons. In addition, a mosque as a center of worship for Muslims as well as a gathering place requires adequate facilities. Adequate facilities in the mosque will make the congregation feel at home. The problem of providing facilities in each mosque is usually constrained by the capacity of the mosque's funding. However, this can be overcome with the effort of the mosque administrators to the donors, both individuals and certain institutions for the provision of facilities. One thing to note is that most mosques are built based on community self-help.